Immunoscintigraphy of human mammary carcinoma xenografts using monoclonal antibodies 12H12 and BM-2 labeled with 99mTc and radioiodine - Brümmendorf, Tim Henrik; Kaul, Sepp; Schuhmacher, Jochen; Baum, Richard P.; Matys, Ronald; Klivényi, Gábor; Adams, Stefan; Bastert, Gunther (Cancer research, 1994)
For immunoscintigraphic localization of human breast cancer two monoclonal antibodies (mabs) 12H12 (immunoglobulin G1) and BM-2 (immunoglobulin G3) were developed. The mabs, directed against two different epitopes on the mucin glycoprotein TAG-12, showed reactivity with 96% of all primary mammary carcinomas. The antibodies were labeled with either 125I or 131I. In addition, 12H12 was directly labeled with 99mTc according to the method of Schwarz and Steinsträsser (A. Schwarz and A. Steinstrasser, J. Nucl. Med., 28: 721, 1987). Biodistribution was measured in female nude mice bearing the human mammary carcinoma SF-15. Both radioiodinated mabs showed similar biodistribution with fast tumor uptake (8.5% injected dose/g at 6 h postinjection), which increased to 10-11% injected dose/g at 24 h and subsequently remained constant up to 120 h. 99mTc-Labeling of the mab 12H12 led to an enhanced tumor uptake of 10.5 and 14% injected dose/g at 6 and 24 h postinjection, respectively, and to significantly accelerated blood clearance of radioactivity. Similar results were obtained with a second mammary tumor (AR-1), while an endometrial tumor (EK-3) showed a 3-fold lower accumulation of radioactivity and no difference in uptake of radioiodinated and 99mTc-labeled 12H12. Scintigraphic imaging of tumor-bearing nude mice with the 99mTc 12H12 at 24 h postinjection clearly demonstrated a diagnostic potential of the new mab for tumor localization and staging.